Prevalence and Characterization of Plasmid Mediated Quinolone Resistance Genes and Class 1 Integrons Among Multidrug-Resistant Escherichia coli Isolates from Chicken Meat. (16th March 2019) - Seo, Kwang Won; Lee, Young Ju
SUMMARY: The increase in multidrug-resistant (MDR) E. coli, which may have been caused by indiscriminate use of antimicrobial agents in humans and animals, has become a serious threat to public health. This study was screened MDR- E. coli isolates from chicken meat in Korea for the presence of plasmid-mediated quinolone resistance (PMQR) genes and class 1 integrons to determine the correlation between PMQR genes and class 1 integrons. Among 248 chicken meat samples, 152 isolates were observed to be positive for E. coli, of which 75 were identified as MDR E. coli . Of the 75 MDR E. coli isolates, 10 (13.3%) were positive for PMQR genes; 7 (9.3%) carried qnrB, 2 (2.7%) carried qnrS, and 1 (1.3%) carried aac(6′)-Ib . A total of 31 of the 75 MDR E. coli isolates also carried class 1 integrons, and 7 different gene cassette arrangements were found in 19 of the 31 class 1 integron-positive isolates. In the comparison of antimicrobial resistance rate, PMQR-positive E. coli had significantly higher resistance rates than PMQR-negative strains to 10 antimicrobial drugs and Integron-positive E. coli had significantly higher resistance than integron-negative E. coli to 11 antimicrobial drugs ( P < 0.05). Our findings suggest that PMQR genes and class 1 integrons are widely distributed in E. coli isolates from chicken meat and that they directly contribute to resistance to diverse antimicrobial agents. Therefore, continuous surveillance of the prevalence of integrons and PMQR genes and their correlation will provide useful information regarding the mechanisms of antimicrobial resistance and may help protect public health.